Modern Methods of Cooperative Learning Technologies in Teaching Biology - Rahmonova Zulfinoy Mamadiyor qizi; Sullieva Suluv Khurramovna (American Journal of Biomedicine and Pharmacy, 2025)
This article explores modern methods of cooperative learning technologies in teaching biology. As traditional teacher-centered approaches give way to student-focused strategies, cooperative learning has emerged as a powerful tool for increasing student engagement, enhancing knowledge retention, and developing communication and collaboration skills. The paper analyzes various contemporary cooperative techniques, such as think-pair-share, jigsaw, group investigations, and peer instruction, in the context of biology education. The effectiveness of these methods in improving both academic performance and interpersonal competencies is discussed. The article also highlights practical applications, classroom strategies, and the role of the teacher as a facilitator in a cooperative learning environment. By implementing modern cooperative learning technologies, biology instruction becomes more interactive, inclusive, and relevant to the 21st-century learner.